Successful Autologous Blood Patch Pleurodesis: A Safe and Useful Treatment for Persistent Pneumothorax in Former Pulmonary Tuberculosis and Aspergillosis in Pregnant Women - Purnama, Nori; Simatupang, Elvando Tunggul Mauliate; Fauzi, Zarfiardy Aksa; Indriani, Sri; Yovi, Indra; Hatta, Hariadi; Zulmaeta (Malang Respiratory Journal, 2024)
Background: Autologous Blood Patch Pleurodesis (ABPP) is one of the treatment options for persistent pleural air leaks especially in patients who are not suitable for surgical intervention. Persistence pneumothorax is defined as pneumothorax of more than five days duration. It is associated with increased morbidity and cost of care. The most widely accepted treatment for it is pleurodesis. Several types of pleurodesis have been proposed, including surgical approaches and the instillation of different chemicals in the intrapleural space. ABPP has proven to be a simple, inexpensive, efficacious and safe method. We present the case of the first patient with Persistent Pneumothorax we have treated Successfully with ABPP. ABPP is currently rarely and uncommonly used, but it provides benefits especially in special conditions with easier, cheaper, and quite effective procedures. Case: A female 35-year-old pregnant women patients with Former Tuberculosis (FTB) come to our hospital with complaints breathlessness and chest pain worsening since 3 days before admitted to our hospital. Chest radiography showed spontaneous pneumothorax with GeneXpert (GE) sputum Mtb Not Detected but there is Aspergillosis from Fungal Culture. Water Sealed Drainage (WSD) was inserted in right pleural for almost 1 month and this patient discharge with pneumostat. One month after that she come again with Persistence Pneumothotax, so that we do the pleurodesis with Blood Patch and get the improvement from clinical status. Antifungals are continued for an initial 4-6 weeks while an outpatient evaluation is conducted. Conclusion: ABPP is a safe, inexpensive and efficacious treatment for persistent pleural air leak. Autologous Blood Patch administration may be considered for patients with Persistent Pneumothorax.